Quality attributes of paddy rice during storage as affected by accumulated temperature - Han, Qian; Chen, Yifan; Liu, Xiuying; Bi, Jie; Zhang, Wei; Zeng, Xuefeng; Wang, Pingping; Shu, Zaixi (Frontiers in Nutrition, 2024)
In actual storage processes of rice, environment temperatures fluctuate rather than remain constant. Accumulated temperature is the sum of temperature during the storage period. In this research, six different temperature-varied conditions with two accumulated temperatures (low intensity: 7200 °C⸱d; high intensity: 9000 °C⸱d) were designed to store rice for 12 months and the stored rice samples were compared in quality. Three low-accumulated temperature conditions were set as follows: No. 4-15 °C for six months followed by 25 °C; No. 5-25 °C for six months followed by 15 °C; No. 8-alternating between 15 °C and 25 °C every two months. Similarly, three high-intensity conditions, No. 6, No. 7, and No. 9, were set with a temperature change from 25 °C to 35 °C. Three constant temperature conditions, No. 1, No. 2, and No. 3, with storage temperature of 15, 25, and 35 °C, respectively, were used as controls. Under temperature-varied conditions, rice demonstrated a decline in germination rate (GR), catalase (CAT) and peroxidase (POD) activities, and an increase in fatty acid value (FAV) as storage time increased. After storage, rice exhibited higher water absorption rate (WAR) and volume expansion rate (VER), but reduced stickiness and sensory scores for appearance, taste and overall quality. Generally, three batches at high-accumulated temperature conditions had lower GR and sensory scores, and higher FAV, WAR, and VER compared to those under low-intensity conditions. Furthermore, variations in the sequence of temperature also affected quality parameters, even at the same accumulated temperature. These findings indicate that under temperature-varied conditions, increased accumulated temperature exacerbates rice deterioration, and different temperature sequences can influence quality at a given accumulated temperature.